Validation of a Korean Version of Fertility Problem Inventory - Ju Hee Kim, RN, PhD; Hye Sook Shin, RN, PhD (Elsevier, 2014)
Purpose: The Fertility Problem Inventory (FPI) is a screening instrument used to identify infertility-related stress. The purpose of this study was to assess the reliability and validity of the Korean version of the FPI. Methods: Forward-backward translation of the FPI from English to Korean was conducted. The translated instrument was pilot-tested and administered to 259 women with infertility. Test-retest reliability was conducted and the internal consistency coefficient was determined. Validity was evaluated through content validity, construct validity with confirmatory factor analysis, discriminant validity, and convergent validity. Results: The internal consistency was satisfactory (Cronbach's alpha = .92, item-total correlations = .60-.92). The overall content validity index was 96.9%, signifying that the FPI had good content validity. The model fit indexes were acceptable (goodness of fit index = .92, adjusted goodness of fit index = .91, normal fit index = .95, comparative fit index = .93, and root mean square error of approximation = .05), indicating good construct validity. The intercorrelations were significant, although low to moderate in size (.20-.59). The correlation between the FPI and depression ranged from .32 to .51 (p < .001), while the correlation between the FPI and the fertility-related quality of life ranged from -.35 to -.58 (p < .001). Conclusion: The Korean version of the FPI has high reliability, and good content, construct, discriminant, and convergent validity. A validated Korean version of the FPI may help nurses identify infertility-related stress and administer appropriate nursing interventions to Korean women with infertility.